ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI MIS AL KHAIRAT DELI TUA - Widiyarti, Gemala; Daliani, Muhammad; Naibaho, Rosin (JURNAL CURERE, 2024)
A good leadership style is a leadership style that is able to provide work motivation to its subordinates to achieve good and maximum performance. The leader's approach to his subordinates cannot be separated from the principal's own leadership style. The leadership style used is conditioned on teacher performance, so the principal's ability is needed to read the situation and respond to it with the right leadership style. Because a good leader is a leader who can protect his subordinates by providing good examples and examples. This research was conducted at the Al Khairat Deli Tua Private Madrasah Ibtidaiyah (MIS). This type of research is qualitative research that uses primary and secondary data. Primary data was obtained through interviews, while secondary data was obtained through existing documents and literature studies. The aim of this research is to see an analysis of the principal's leadership style on teacher performance at MIS Al Khairat.